PERLUASAN KOMPETENSI PERADILAN TATA USAHA DALAM UNDANG-UNDANG ADMINISTRASI PEMERINTAHAN - Barhamudin, Barhamudin; Bustomi, Abuyazid (Faculty of Law, University of Palembang, 2022)
The purpose of this study is to explain the field of State Administration law since the promulgation of the State Administration Law 30 of 2014. This research is a legal research with a conceptual approach, a legal approach. This research data is secondary data which includes primary legal documents, secondary legal documents and tertiary legal documents. As a consequence, Law Number 30 of 2014 concerning the Implementation of State Administrative Courts has made major changes to the absolute jurisdiction of the State Administrative Court, namely the absolute jurisdiction of the State Administrative Court. state administrative decisions (beschikking), accompanied by courts and complaints to the state administrative courts.